Site-directed Mutagenesis Identifies Residues Involved in Ligand Recognition in the Human A(2a) Adenosine Receptor - Kim, Jeongho (1995)
The A(2a) adenosine receptor is a member of the G-protein coupled receptor family, and its activation stimulates cyclic AMP production. To determine the residues which are involved in ligand binding, several residues in transmembrane domains 5–7 were individually replaced with alanine and other amino acids. The binding properties of the resultant mutant receptors were determined in transfected COS-7 cells. To study the expression levels in COS-7 cells, mutant receptors were tagged at their amino terminus with a hemagglutinin epitope, which allowed their immunological detection in the plasma membrane by the monoclonal antibody 12CA5. The functional properties of mutant receptors were determined by measuring stimulation of adenylate cyclase. Specific binding of [(3)H]CGS 21680 (15 nm) and [(3)H]XAC (4 nm), an A(2a) agonist and antagonist, respectively, was absent in the following Ala mutants: F182A, H250A, N253A, I274A, H278A, and S281A, although they were well expressed in the plasma membrane. The hydroxy group of Ser-277 is required for high affinity binding of agonists, but not antagonists. An N181S mutant lost affinity for adenosine agonists substituted at N(6) or C-2, but not at C-5′. The mutant receptors I274A, S277A, and H278A showed full stimulation of adenylate cyclase at high concentrations of CGS 21680. The functional agonist potencies at mutant receptors that lacked radioligand binding were >30-fold less than those at the wild type receptor. His-250 appears to be a required component of a hydrophobic pocket, and H-bonding to this residue is not essential. On the other hand, replacement of His-278 with other aromatic residues was not tolerated in ligand binding. Thus, some of the residues targeted in this study may be involved in the direct interaction with ligands in the human A(2a) adenosine receptor. A molecular model based on the structure of rhodopsin, in which the 5’-NH in NECA is hydrogen bonded to Ser-277 and His-278, was developed in order to visualize the environment of the ligand binding site.